A single layer dual band Reflectarray antenna for millimeter-wave application - Ajitesh; Srivastava S.K.; Singh A.; Bharati R.; Sharma A.K.; Meshram M.K. (My University, 2025)
A single layer, dual-band Reflectarray antenna is presented. The proposed reflectarray consist of two different elements, cross-dipole at 28 GHz and, the square ring with inner patch at 38 GHz on the same aperture. By varying the size of these elements, the required phase shift at these bands is obtained independently. The simulated realized gain is 26.3 dBi at 28 GHz and 28.8 dBi at 38 GHz and aperture efficiency are 25% at 28 GHz and 24% at 38 GHz. The side lobe level is -15dB at 28GHz and -22.5dB at 38GHz. The proposed antenna can be a good candidate in Ka band for 5G applications. © 2022 IEEE.